Brain Activity Reflects Subjective Response to Delayed Input When Using an Electromyography-Controlled Robot - Kim, Hyeonseok; Kim, Yeongdae; Miyakoshi, Makoto; Stapornchaisit, Sorawit; Yoshimura, Natsue; Koike, Yasuharu (Frontiers in Systems Neuroscience, 2021)
In various experimental settings, electromyography (EMG) signals have been used to control robots. EMG-based robot control requires intrinsic parameters for control which makes it difficult for users to understand the input protocol. When a proper input is not provided, the response time of the system varies; as such, the user’s subjective delay should be investigated regardless of the actual delay. In this study, we investigated the influence of the subjective perception of delay on brain activation. Brain recordings were taken while subjects used EMG signals to control a robot hand, which requires a basic processing delay. We used muscle synergy for the grip command of the robot hand. After controlling the robot by grasping their hand, one of four additional delay durations (0 ms, 50 ms, 125 ms, and 250 ms) was applied in every trial, and subjects were instructed to answer whether the delay was natural, additional, or whether they were not sure. We compared brain activity based on responses (“sure” and “not sure”). Our results revealed a significant power difference in the theta band of the parietal lobe, and this time range included the interval in which they could not feel the delay. Our study provides important insights that should be considered when constructing an adaptive system and evaluating its usability.